A study on the impact of logistic strategy towards customer satisfaction: A study of BC Petrochemical, Malaysia / Normaslindahwati Rasib - Rasib, Normaslindahwati (Faculty of Business and Management, 2008)
This research is about a study on the impact of Logistic Strategy towards Customer Satisfaction. Strategies such as transportation, warehousing, order processing, inventory control and packaging have been identified in order to investigate whether or not these strategy have correlation with customer satisfaction. The survey is conducted for Bc Petrochemical customers such as Petronas Gas Malaysia, Petronas Carigali Malaysia, Sabah & Sarawak Shell, Sapura Holding, Exxonmobil Malaysia and many more. Those companies come from oil and gas sector. The sample size for this study is 35 customers who are dealing business with Bc Petrochemical. There are 35 questionnaire were distribute and all 35 questionnaire were returned. Data obtained using two methods that are primary and secondary data. The primary data was questionnaire that required the respondents to answer the questionnaire that contain elements which potentially have relationship with customer satisfaction. Data are analyzed using reliability test, frequency analysis, and correlation analysis through SPSS Program. The result shows that all three out of five strategies from independent variables were significant. The strategies are warehousing, packaging and order processing. Meanwhile transportation and inventory control has no significant correlation with customer satisfaction.